An examination of the factors fueling migration amongst Community Service practitioners - Candice Reardon; Gavin George (AOSIS, 2014)
Background: Research is needed in order to understand the potential influence of the Bilateral Agreement between South Africa and the United Kingdom (UK), as well as other more recent international and local policies restricting movement of South African health workers abroad; and to determine what effect they have on the migration intentions and plans of health professionals in South Africa. Aim: The aims were to (1) explore the migration intentions and the factors that influence these intentions amongst Community Service (CS) nurses and doctors; (2) explore their views and opinions about the Bilateral Agreement between the UK and South Africa (SA) and other UK policies around the recruitment and employment of foreign health professionals; and (3) understand the impact of these policies on the migration plans of these CS doctors and nurses. Method: Qualitative focus groups and interviews were conducted with 23 CS doctors and nurses. To supplement this, 6 interviews were conducted with nurses and a doctor who had worked in the UK. Results: A higher disposition toward moving abroad was apparent amongst those who had experienced a challenging and frustrating CS year. Poor working conditions, including long work hours, high patient loads and inadequate resources and equipment, as well as low salaries and the perceived ambivalence of the government to the complaints of health practitioners, were influencing decisions to migrate abroad. Conclusion: The findings suggest that government efforts to better manage, recognise and respect the work and contribution of health professionals to the country would go a long way toward retaining health professionals.